2016
DOI: 10.2298/hemind150807001m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of biodiesel from sunflower oil over potassium loaded alumina as heterogeneous catalyst: The effect of process parameters

Abstract: Heterogeneous catalysis is in recent focus of research for biodiesel production from vegetable oils because of advantages such as easy separation and reuse of catalysts, although homogeneous catalysis is most commonly used method. The aim of this study was preparation of γ-Al 2 O 3 supported by modified sol-gel procedure, synthesis of the KI/Al 2 O 3 catalyst and testing its activity in the transesterification of sunflower oil with methanol. Influences of different process parameters on conversion of sunflower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 38 publications
9
10
1
Order By: Relevance
“…Loading of potassium iodide on alumina can lead to a high activity of the catalyst in the transesterification reaction, as it was shown by recent studies [22][23][24]. Marinkovic et al [24] have found that the catalysts prepared by loading 37 wt.% of KI onto Al 2 O 3 and calcinated at 1043 K for 3h resulted in the highest conversions of 99.99% to fatty acids methyl-esters under relatively mild conditions [24].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Loading of potassium iodide on alumina can lead to a high activity of the catalyst in the transesterification reaction, as it was shown by recent studies [22][23][24]. Marinkovic et al [24] have found that the catalysts prepared by loading 37 wt.% of KI onto Al 2 O 3 and calcinated at 1043 K for 3h resulted in the highest conversions of 99.99% to fatty acids methyl-esters under relatively mild conditions [24].…”
Section: Introductionmentioning
confidence: 94%
“…The KI/Al 2 O 3 catalysts were prepared by incipient wetimpregnation of γ-Al 2 O 3 with desired amounts of potas-sium iodide aqueous solutions to the nominal amount of KI 37 wt.%. This procedure was conducted for 2 h. After that, the catalysts were dried at 120 °C for 3 h, and then the catalysts were activated by heating at 770 °C with the temperature rate of 10 °C/min for 3 h [24].…”
Section: Preparation Of Potassium Iodide γ-Al 2 O 3 -Supported Catalystsmentioning
confidence: 99%
See 3 more Smart Citations